Cyberpunk as a Metacultural Movement: Philosophical-Cultural Analysis - Валерій Кушнарьов (Культура і мистецтво у сучасному світі)
The aim of the article is to analyse the phenomenon of modern mass culture and during this analysis find out its ontological status including scientism-technological imperatives of cyberculture and ideas of transhumanism. Results. Cyberpunk is an interesting, functional and new (in comparison with classical examples) form of mass culture, cultural-ideological movement, and sphere of translation and the intersection of protest ideas and meanings, due to its genre and sectoral pluralism (science fiction, film industry, music, design, video games, fashion, ideology, etc.), and also logics of technodeterminism, is still an important factor of transformation cultural-art space in the 21st century. Scientific novelty. In the article, for the first time, realised the philosophical-cultural analysis of cyberpunk including its peculiarities as a literary genre, phenomenon of mass culture and aesthetics. Conclusions. It is proved that cyberpunk appeared as a genre of science fiction literature in the 1960s-1970s and then later through conceptualisation of ideas in the 80s and agreeing of transcendental impulses counterculture of the 60s with computerisation and the specifics of technological evolution in the 90s, has evolved to the level of a metacultural movement. As the latter, it encompasses the literary genre, the film and fashion industry, architecture and graphic design (with a special aesthetic), technoanthropology, futurology and identity theory, and ideological discourse. It is confirmed that thanks to protest as a manifestation of freedom, the actualisation of the problem of corporeality, and dystopian high-tech projections, with the help of postmodern relativism and poststructuralist rhizomorphism, cyberpunk annihilates modern cultural narratives, thus creating many risks, including the potential formation of pathological forms of identification, declarative asociality, and cyber-prosthetics, which often develop into horrific manifestations of dehumanisation.